Mixed‐Methods Study of Uptake of the Extension for Community Health Outcomes (ECHO) Telemedicine Model for Rural Veterans With HIV. Issue 3 (24th August 2016) - Moeckli, Jane; Stewart, Kenda R.; Ono, Sarah; Alexander, Bruce; Goss, Tyler; Maier, Marissa; Tien, Phyllis C.; Howren, M. Bryant; Ohl, Michael E.
Abstract: Purpose: Extension for Community Health Outcomes (ECHO) is a provider‐level telemedicine model successfully applied to hepatitis C care, but little is known about its application to Human Immunodeficiency Virus (HIV) care. We performed a mixed‐methods evaluation of 3 HIV ECHO programs in the Veterans Health Administration, focusing on uptake by primary care clinics and veterans. Methods: Administrative data were used to assess program uptake, including adoption (ie, proportion of primary care clinics participating) and reach (ie, proportion of eligible veterans participating). Veterans were considered eligible if they had an HIV diagnosis and lived nearer to a primary care clinic than to the HIV specialty clinic. We interviewed 31 HIV specialists, primary care providers (PCPs), and administrators engaged in HIV ECHO, and we analyzed interview transcripts to identify factors that influenced program adoption and reach. Findings: Nine (43%) of 21 primary care clinics adopted HIV ECHO (range 33%‐67% across sites). Program reach was limited, with 47 (6.1%) of 776 eligible veterans participating. Reach was similar among rural and urban veterans (5.3% vs 6.3%). In interviews, limited adoption and reach were attributed partly to: (1) a sense of "HIV exceptionalism" that complicated shifting ownership of care from HIV specialists to PCPs, and (2) low HIV prevalence and long treatment cycles that prevented rapid learning loops for PCPs. Conclusions: There was limited uptake of HIV ECHO telemedicine programs in settings where veterans historically traveled to distant specialty clinics. Other telemedicine models should be considered for HIV care.